Assessing Phraseological Development in Word Sequences of Variable Lengths in Second Language Texts Using Directional Association Measures. Issue 2 (11th February 2019) - Chen, Alvin Cheng‐Hsien
Abstract: This study evaluated second language (L2) phraseological development using a directional association measure (delta P) that assesses the directional formulaicity of recurrent multiword combinations. The study examined (a) whether learners develop their sensitivity to the distributional properties of recurrent multiword combinations as their proficiency grows and (b) how this development is mediated by the directionality of lexical associations and combination length. The formulaicity of recurrent multiword combinations was assessed from bigrams to five‐grams in L2 argumentative essays by assigning them forward and backward delta P scores, computed from two representative native speaker corpora. Mixed‐effect modeling of delta P variation showed that formulaicity increased with proficiency. Although participants generally showed higher backward‐directed formulaicity, they demonstrated a more pronounced growth in forward‐directed formulaicity across proficiencies. Backward‐directed formulaicity, however, improved at a slower rate, suggesting sophistication in phrasal complexity. Longer sequences mitigated these directional differences. Abstract :